2001
DOI: 10.1093/intimm/13.12.1595
|View full text |Cite
|
Sign up to set email alerts
|

Human MD-2 confers on mouse Toll-like receptor 4 species-specific lipopolysaccharide recognition

Abstract: Toll-like receptor 4 (TLR4) recognizes lipopolysaccharide (LPS). MD-2 is associated with TLR4 and imparts LPS responsiveness to it. Little is known, however, as to whether MD-2 directly regulates LPS recognition by TLR4. To address the issue, we took advantage of a species-specific pharmacology of lipid IVa, an analogue of lipid A. Lipid IVa acted agonistically on mouse (m) TLR4/MD-2 but not on human (h) TLR4/MD-2. Lipid IVa antagonized the agonistic effect of lipid A on hTLR4/MD-2. We examined the chimeric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
169
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 233 publications
(182 citation statements)
references
References 24 publications
9
169
1
3
Order By: Relevance
“…TLR4 is involved in this ligand-specific recognition of LPS (17,18). Recently, the involvement of MD-2 in this ligand-specific recognition of LPS was also demonstrated (19). Similar to lipid IVa, Taxol mimics the action of LPS on mouse cells but not on human cells.…”
Section: Identification Of Mouse Md-2 Residues Important Formentioning
confidence: 95%
“…TLR4 is involved in this ligand-specific recognition of LPS (17,18). Recently, the involvement of MD-2 in this ligand-specific recognition of LPS was also demonstrated (19). Similar to lipid IVa, Taxol mimics the action of LPS on mouse cells but not on human cells.…”
Section: Identification Of Mouse Md-2 Residues Important Formentioning
confidence: 95%
“…On the other hand, an antagonistic effect of the tetraacylated biosynthetic precursor of lipid A, lipid IVa, on LPS-induced cell activation has been indicated [25]. Interestingly, the lipid A analog has been shown to be antagonistic toward human cells and agonistic with murine cells [26]; it was recently demonstrated that MD-2 is associated with this species-specific recognition of LPS [27]. To determine whether Tm-Gp has an antagonistic effect on TLR4/MD-2 and TLR2, we examined the effect of Tm-Gp on NF-â€č B activation in Ba/mTLR4/mMD-2 cells stimulated with various TLR4 ligands, including LPS, Escherichia colitype synthetic lipid A (compound 506), and Taxol, and PGN as a TLR2 ligand (Fig.…”
Section: Effect Of Tm-gp On Cell Activation By Tlr4 and Tlr2 Ligandsmentioning
confidence: 99%
“…Lipid A is an agonist in most species whereas lipid IVa, while being an agonist in the mouse, is an antagonist for human cells (21,24). This suggests that lipid IVa is able to bind to human TLR4/MD-2 but is 3 Address correspondence and reprint requests to Dr. Clare Bryant, Department of Veterinary Medicine, University of Cambridge, Madingley Road, Cambridge, CB3 OES, U.K. E-mail address: ceb27@cam.ac.uk 4 Abbreviations used in this paper: LRR, leucine-rich repeat; EH, chimera in which a human region is engineered into an equine framework; HE, chimera in which an equine region is engineered into a human framework.…”
mentioning
confidence: 99%
“…There are marked differences among mammalian species in the activities of different types of lipid A that behave as agonists or antagonists at the MD-2/TLR4 complex (21)(22)(23). Lipid A is an agonist in most species whereas lipid IVa, while being an agonist in the mouse, is an antagonist for human cells (21,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation